Pengembangan Model Proses Bisnis Berbasis Aliran Proses dan Aliran Data - Fairuzia, Arifah; Yaqin, Muhammad Ainul; El-Sulthan, Maulana Muhammad; Amini, Fauziyah (Jurasik (Jurnal Riset Sistem Informasi dan Teknik Informatika), 2020)
Data Objects and Data Stores are two notations that exist in BPMN, but in their implementation, in XPDL Data Objects and Data Stores still do not fulfill their function as data stream loaders. So data injection is needed so that the business process model can contain process flow and data flow. The purpose of this study is to develop business process models so that business process models can contain process flow and data flow. The business process model can contain process flow and data flow if there is data injected through XPDL from the business process model. Data injection is performed on XPDL Data Objects, Data Stores and transitions. Before injecting data into XPDL, the data to be injected is analyzed first. After being analyzed, the data is injected into XPDL Data Objects, Data Stores and transitions. After the data is injected, XPDL is tested whether it can be reopened as a business process model or not with Bizagi software. The results obtained are XPDL files that can inject data in the Data Store, Data Objects and transitions. XPDL that has been injected by the data in the test can be reopened in Bizagi software. The conclusion of this research is the process flow and data flow in the business process model can be developed.